Upaya peningkatan pengetahuan tentang HIV dalam rangka menurunkan stigma orang dengan HIV pada bidan di Yogyakarta - Nanik Setiyawati; Niken Meilani (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
Introduction. Cases of HIV / AIDS in middle and low income countries are very many and cause death. Indonesia is one of the countries with an increase in HIV cases in the 15-49 age group in 2001-2011 by more than 25%. One of the biggest obstacles in the prevention and control of HIV / AIDS is the high stigma and discrimination against people with HIV / AIDS (PLWHA), including stigma by health workers. The majority of midwives get information about HIV / AIDS through lectures and only 5% say they get information through socialization after work. Objective: The aim of this activity is to Increase knowledge of midwives about HIV AIDS and PLWHA Dedicated partners: Midwife and NGO Victory Plus Method: This community service is divided into 2 meetings. At the first meeting the pre-test was given, then the material by the Victory Plus NGO and the post test ended. The second meeting with Focus Group Discussion (FGD) with the theme of the Stigma of PLWHA with pre-post test Results: There was an increase in the average level of knowledge before and after the previous intervention 19.7 rose to 21.5 with a value of P = 0.029. This shows an increase in the average level of knowledge and statistically proven interventions can increase the level of knowledge. Conclusion: This service is effective in increasing the level of knowledge of midwives about HIV which was previously felt to be lacking and reducing the stigma of PLWHA so that midwives are able to provide services to PLHIV especially women in order to carry out HIV Prevention Programs from mother to child.